2010
DOI: 10.1002/ar.21316
|View full text |Cite
|
Sign up to set email alerts
|

Identification of N‐Acetylgalactosamine in Carbohydrates of Xenopus laevis Testis

Abstract: Identification of glycans in amphibian testis has shown the existence of N-acetylgalactosamine (GalNAc)-containing carbohydrates. Labeling of the sperm acrosome with GalNAc-binding lectins has allowed the identification of GalNAc-containing glycans in this organelle. Futhermore, this specific labeling of the acrosome has allowed the study of acrosomal biogenesis by lectin histochemistry. However, the testis of Xenopus laevis has never been analyzed by lectin histochemistry to locate GalNAc-containing glycoconj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 62 publications
1
10
0
4
Order By: Relevance
“…Lectin histochemical techniques have been widely used to study the pattern of the glycoconjugates present in the cells of the seminiferous epithelium in many species of vertebrate, including amphibians (Valbuena et al. , ,b), fish (Liguoro et al. ; Desantis et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lectin histochemical techniques have been widely used to study the pattern of the glycoconjugates present in the cells of the seminiferous epithelium in many species of vertebrate, including amphibians (Valbuena et al. , ,b), fish (Liguoro et al. ; Desantis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lectin histochemical techniques have been widely used to study the pattern of the glycoconjugates present in the cells of the seminiferous epithelium in many species of vertebrate, including amphibians (Valbuena et al 2010(Valbuena et al , 2011a, fish (Liguoro et al 2004;Desantis et al 2010), birds (Ballesta et al 1991;Bakst et al 2007;Pel aez and Long 2008), mammals (Arya and Vanha-Perttula 1985;Calvo et al 2000;Pinart et al 2001;Morales et al 2002;Desantis et al 2006;Parillo et al 2012) and humans (Arenas et al 1998). This histochemical technique has recently been used to identify changes in the pattern of glycoconjugates of various cell types in apoptosis (Taatjes et al 2008), in particular lectins with affinity for a-D-mannose and b-D-galactose (Bilyy et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In some previous works, we have shown that the acrosome of Xenopus is unreactive for other Fucose‐, Galactose‐ and N ‐acetylgalactosamine‐binding lectins (Valbuena et al. , ,b). The acrosome is a specialized cell organelle that has plenty of glycoproteins and, in most species, is very reactive to a lot of lectins (Yamamoto, ; Arya & Vanha‐Perttula, , , ; Lee & Damjanov, ; Malmi & Söderström, ; Ballesta et al.…”
Section: Discussionmentioning
confidence: 79%
“…Xenopus laevis increasingly serves as an in-vitro and in-vivo model for the screening of Endocrine Disruptor Chemicals (EDCs) that affect hypophysis and thyroid glands as well as gonads, and as a model animal species to study reproductive toxicity of phytoestrogens (Cong et al, 2006). For these reasons, gonadal histomorphology (Cevasco et al, 2008;Kalt, 1976) and histochemistry (Valbuena et al, 2012(Valbuena et al, , 2010Valbuena, Alonso, Diaz Flores, et al, 2011;Valbuena, Alonso, Madrid, & Diaz Flores, and Saez, 2011b) are well documented in adult Xenopus. However, only one of the above-mentioned studies has paid attention to the testicular blood vessels (Cevasco et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy, morphology, fine structure, histochemistry and endocrine regulation of the anuran testes have been studied in great detail (e.g., Lofts, ; Duellman & Trueb, ; Valbuena, Madrid, Hernandez, & Saez, ; Valbuena, Alonso, Diaz Flores, Madrid, & Saez, ; Valbuena et al, ; Villagra, Ramos, Cisint, Crespo, & Fernandez, ). However, little is known on the vascular anatomy of the anuran testes.…”
Section: Introductionmentioning
confidence: 99%